Violence and non-violence in Bonhoeffer's theology - András Csepregi (Opuscula Theologica et Scientifica, 2025)
At 2013 a new debate started about whether Bonhoeffer, who in his mid-twenties turned into a devoted pacifist Christian changed his mind later as agreeing to kill Hitler or stayed a representative of non-violence until his violent death. Some interpreters, the biographer Eberhard Bethge among them, represent the change, arguing, that this change was a sort of development as Bonhoeffer’s sense of the world, responsibility and theological reflection matured. Other interpreters, for example, Mark Thiessen Nation, author of Bonhoeffer the Assasin? Think that Bonhoeffer did not change his preference for non violence. I my paper I call this positions a “development-type” and a “consistency-type” of argumentations. Although I express my preference for the latter, I do not engage the debate between these standpoints here – I save it for the second part of my essay. Instead, I suggest an examination of the background of Bonhoeffer’s theological decisions, reflecting on the atmosphere of his family as well as the interpretation of Luther inherited from 19th century German Protestant theology. Both had a rather peculiar focussing on death that became a tacit dominant motif for Bonhoeffer’s life and theology. In the year of the 80th anniversary of his violent death I think it is time to have a closer look at it.